The efficiency of the London Gold Fixing: From Gold Standard to hoarded commodity (1919-68) - Fergal A. O'Connor; Brian M. Lucey (The European Association for Banking and Financial History (EABH), 2023)
This paper presents and explains the newly rediscovered and transcribed daily market gold price from 1919-1968 for the world's main gold market during the period, the London Gold Fixing Auction. The paper highlights several novel features previously not discussed in the literature, such as gold prices fluctuating at the daily Gold Fixing even during the two Gold Standard periods when gold prices are often thought of as 'fixed'. It also describes key turning points during the evolution of the Gold Fixing such as its formation and the daily price reactions when Britain went on or came off the Gold Standard. This paper offers the first long-run examination of the weak form efficiency of the Gold Fixing from its inception, at a time when gold was the centre of the world's monetary system. We find that the Gold Fixing price was informationally efficient at its inception in 1919 but by the 1930s, when there was increased buying for speculation and investment (referred to as hoarding) the market became more predictable and inefficient. We also find that the market was inefficient during gold standard periods when central banks were limiting gold's ability to react to new information.
Keywords: F3; G1; G2; N2; Q3; 330; Daily Gold Price Data; London Market; Market Efficiency; Gold Fixing; Hoarding